Raising Wood Ducks (Aix sponsa)—It Can Be Done - Goodman, Michele (Wildlife Rehabilitation Bulletin, 2009)
The care and rehabilitation of orphaned wood ducks (Aix sponsa) can be challenging and frustrating to wildlife rehabilitators. By understanding the behavioral differences that separate wood ducks from dabbling ducks and by changing the way rehabilitators perceive and care for wood ducklings, greater success can be achieved.